Bisabolane sesquiterpenes from Clausena sanki with their potential anti-inflammatory activities. Issue 24 (16th December 2020) - Hu, Shi; Ma, Yan-Lei; Guo, Jia-Ming; Wen, Qing; Yan, Gui; Yang, Shuo; Fu, Yan-Hui; Liu, Yan-Ping
Abstract: The investigation on the stems and leaves of Clausena sanki led to the isolation of a previously undescribed bisabolane sesquiterpene, clausemargic A (1 ), together with six known analogues (2 –7 ). The structure of 1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. All known compounds (2 –7 ) were isolated from C. sanki for the first time. All isolated compounds were evaluated for their anti-inflammatory activities via examining the inhibitory activity on nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells in vitro . Compounds 1 –7 showed significant inhibitory activities with IC50 values comparable to that of hydrocortisone. Graphical Abstract: